EVALUATION OF POLIO IMMUNIZATION COVERAGE AND ACUTE FLACCID PARALYSIS SURVEILLANCE IN EAST JAVA, INDONESIA, 2018-2022: Evaluasi Cakupan Imunisasi Polio dan Surveillance Paralisis Flaksida Akut di Jawa Timur, Indonesia Tahun 2018-2022 - Tarawally, Abubakar; Hargono, Arief; Susanto, Hugeng; Wulandari, Wahyu (Jurnal Berkala Epidemiologi, 2024)
Background: Indonesia has successfully eradicated wild poliovirus since 2005 using robust immunization and AFP surveillance programs. However, circulating vaccine-derived poliovirus type 2 has challenged these commitments, followed by the 2024 outbreak in East Java. Purpose: The study aims to analyze the polio eradication initiative by assessing polio immunization coverage and AFP surveillance in East Java. Methods: A descriptive, quantitative study design and retrospective analysis of polio immunization coverage and AFP surveillance indicators from the Provincial Health Office, East Java, from 2018–2022. The data was collected and analyzed using Excel, EpiInfo7, and Health Mapper software. Results: OPV4 coverage ranged from 89.95% to 100.76%, while IPV coverage ranged from 73.98 % to 94.18% from 2018 to 2020; the proportion of districts and cities for IPV coverage increased from 0% in 2018 to 44.74% in 2022, below the 95% WHO target. Of the 826 cases of AFP reported, 820 (99.27%) were actual AFP cases <15 years of age, with most (49.02%) being <5 years of age. Non-polio AFP rates ranged from 0.80 in 2020 to 2.59 in 2022 per 100,1000 <15 years of age, with the proportion of districts and cities slightly declining from 55.26% in 2018 to 50% in 2022. The annual mean percentage of AFP-adequate specimens is 61.15%, with the proportion of districts and cities significantly declining from 31.58% in 2018 to 10.53% in 2022, below the 80% target. Conclusion: IPV immunization coverage and AFP surveillance indicators are below the WHO-recommended targets across districts and cities in East Java.